Direct-to-consumer laboratory testing (DTCT): challenges and implications for specialists in laboratory medicine: opinion paper - Orth, Matthias; Vollebregt, Erik; Trenti, Tomaso; Shih, Patti; Tollanes, Mette; Sandberg, Sverre (Clinical chemistry and laboratory medicine, 2023)
In vitro diagnostics (IVD) testing is a powerful tool for medical diagnosis, and patients‘ safety is guaranteed by a complex system of personnel qualification of the specialist in laboratory medicine, of process control, and legal restrictions in healthcare, most of them under national regulation. Direct-to-consumer laboratory testing (DTCT) is testing ordered by the consumer and performed either by the consumer at home or analysis of self-collected samples in a laboratory. However, since DTCT are not always subject to effective competent authority oversight, DTCT may pose risks to lay persons using and relying on it for healthcare decision-making. Laboratory medicine specialists should be very cautious when new DTCTs are introduced. As qualified professionals, they should feel obliged to warn and educate patients and the public about the risks of inappropriate and harmful DTCT.
Online veröffentlicht: 26. Dezember 2022
Gesehen am 15.07.2024